Pathogens Causing Respiratory Tract Infections in Children Less Than 5 Years of Age in Senegal. (December 2019) - Knobbe, Rebecca B; Diallo, Abdallah; Fall, Amary; Gueye, Aida D; Dieng, Assane; van Immerzeel, Tabitha D; Ba, Abou; Diop, Amadou; Diop, Abdoulaye; Niang, Mbayame; Boye, Cheikh SB
Introduction: While acute respiratory tract infections are the main cause of paediatric mortality and morbidity worldwide, pathogen patterns shift due to factors such as hygiene, vaccinations, and antibiotic resistance. Knowledge about current cause of respiratory infections is lacking, particularly in low- and middle-income countries. The aim of this study was to identity the various respiratory pathogens causing acute respiratory tract infections in children below 5 years of age visiting a sub-urban primary care clinic in Senegal. Methods: A case-control study was performed in September and October 2018. Oropharyngeal swabs were collected from cases; infants with fever and respiratory symptoms, and controls; children involved in the vaccination programme. Viral identification was conducted by polymerase chain reaction for 21 different viruses; bacteria were identified by culture studies. Associations between microorganisms, acute respiratory infection and severity of disease were calculated by multivariate regression adjusting for confounders such as age, sex, and living area. Results: Overall, 102 cases and 96 controls were included. Microorganisms were detected in 90.1% of cases and 53.7% of controls ( P < .001). Influenza virus A (including H1N1), influenza virus B, respiratory syncytial virus (RSV), and Streptococcus pneumoniae were independently associated with acute respiratory tract infections. Co-detection of two or more pathogens was present in 49.5% of cases; 31.7% of cases had a pneumonia and 90.2% was treated with antibiotics. Conclusions: This case-control study in a primary care setting in sub-Saharan Africa found influenza virus A and B, RSV, and S pneumoniae to be the main causes of acute respiratory tract infections in children below 5 years of age. We recommend evaluation of antibiotics prescription behaviour in this setting.